2007
DOI: 10.1021/ja068551y
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Library of BODIPY-Based Environmental Polarity Sensors Utilizing Photoinduced Electron-Transfer-Controlled Fluorescence ON/OFF Switching

Abstract: We systematically examined the mechanism of the solvent polarity dependence of the fluorescence ON/OFF threshold of the BODIPY (boron dipyrromethene) fluorophore and the role of photoinduced electron transfer (PeT). In a series of BODIPY derivatives with variously substituted benzene moieties at the 8-position, the oxidation potential of the benzene moiety became more positive and the reduction potential of the BODIPY fluorophore became more negative as the solvent polarity was decreased; consequently, the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
330
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(347 citation statements)
references
References 31 publications
15
330
0
2
Order By: Relevance
“…The selection of the target molecules is based on an expected change in the optical properties of the probe based on a photoelectron transfer (PeT) mechanism of fluorescence quenching. We noted that Munkholm previously reported that fluoresceinamine has a quenched fluorescence due to amine group, but conversion of amine to an amide restored the full fluorescent indicator properties of fluorescein [15][16][17][18]. Gabe and his coworkers previously reported some computational studies [19] on calculation of the HOMO (highest occupied molecular orbital) energy level of different PeT donors for the boron dipyrromethene (BDP) chromophore and noted a threshold value for the HOMO that would result in quenched fluorescence.…”
Section: Introductionmentioning
confidence: 95%
“…The selection of the target molecules is based on an expected change in the optical properties of the probe based on a photoelectron transfer (PeT) mechanism of fluorescence quenching. We noted that Munkholm previously reported that fluoresceinamine has a quenched fluorescence due to amine group, but conversion of amine to an amide restored the full fluorescent indicator properties of fluorescein [15][16][17][18]. Gabe and his coworkers previously reported some computational studies [19] on calculation of the HOMO (highest occupied molecular orbital) energy level of different PeT donors for the boron dipyrromethene (BDP) chromophore and noted a threshold value for the HOMO that would result in quenched fluorescence.…”
Section: Introductionmentioning
confidence: 95%
“…In some of designed complexes emission and absorption wavelengths are shifted to NR-IR spectral region. These results, are defined as NIR dyes (red emitting fluorescent dyes), appear on the spectral properties of the compounds [13]. Spectrums can be found in Supporting Information in Figure S1.…”
Section: Uv-visible Absorption and Emission Spectra Of The Compoundsmentioning
confidence: 99%
“…F denotes the area under the fluorescence band (F = a I fl (λ), where I fl (λ) is the fluorescence intensity at each emission wavelength), A denotes the absorbance at the excitation wavelength, and n is the refractive index of the solvent [32]. NMR spectra were obtained as DMSO-d 6 or CDCl 3 solutions using Varian Mercury 300 MHz NMR spectrometer and the chemical shifts are quoted relative to the solvent peaks.…”
Section: Generalmentioning
confidence: 99%